Long-term outcome of lesional posterior cortical epilepsy surgery in adults. Issue 7 (25th March 2009) - Elsharkawy, A E; El-Ghandour, N M F; Oppel, F; Pannek, H; Schulz, R; Hoppe, M; Woermann, F G; Nayel, M; Issa, A; Ebner, A
Abstract : Objective: The aim of this study was to evaluate the short- and long-term seizure outcome and to find predictors of outcome after epilepsy surgery in lesional posterior cortical epilepsies (PCEs). Methods: The operative outcome in 80 consecutive adult patients with lesional PCEs who underwent resective surgery for intractable partial epilepsy between 1991 and 2006 was retrospectively studied. Results: The probability of remaining in Engel Class I was 66.3% (95% CI 60 to 72) at 6 months, 52.5% (95% CI 47 to 57) at 2 years, 52.9% (CI 45 to 59) at 5 years and 47.1% (CI 42 to 52) at 10 years. Factors predicting poor outcome were the presence of a somatosensory aura, extraregional spikes, incomplete resection, interictal epileptiform discharge (IED) in EEG 6 months and 2 years postsurgery, history of generalised tonic-clonic seizure (GT-CS) and the presence of focal cortical dysplasia in the resected specimen. Factors predicting good outcome were childhood onset of epilepsy, short epilepsy duration, ipsilateral spikes, visual aura, presence of well-circumscribed lesion in preoperative MRI and a pathologically defined tumour. In the multivariate analysis, predictors were different in the long and short term as follows: incomplete resection as proven by postoperative MRI (hazard ratio (HR) 2.059 (CI 1.19 to 3.67)) predicts seizure relapse in short-term follow-up. The presence of IED in the EEG performed 6 months after surgery (HR 2.3 (CI 1.128 to 4.734)) predicts seizure relapse in the long-term fellow-up. However, the absence of a history of GT-CS independently predicts seizure remission in short- and long-term follow-up. Conclusions: Surgery in PCEs proved to be effective in short- and long-term follow-up. Lesional posterior cortical epilepsy may be a progressive process in a substantial number of cases.